KAJIAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 1 SOLOK PADA PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA - Maharani, Fitria (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students need to demonstrate that they can communicate mathematically. Class IX pupils at SMP Negeri 1 Solok continue to demonstrate a low level of competence, nonetheless. The chosen strategy makes use of Geogebra to execute the Problem Based Learning (PBL) methodology. The purpose of this research was to compare the performance of students in ninth grade at SMP Negeri 1 Solok who received direct teaching with those who received PBL models with the help of geogebra. A non-equivalent control group that received just posttests was used in the quasi-experimental study. We may reject the null hypothesis (H0) because the t-test yielded a P-value of 0.008. In comparison to direct learning, the results show that the PBL paradigm, when augmented with geogebra, is more effective..Keywords– Problem Based Learning Model, Geogebra, Mathematical Communication, Direct Learnin